Developments allergy in 2019 through the eyes of Clinical and Experimental Allergy, Part II clinical allergy. Issue 12 (1st December 2020) - Roberts, Graham; Almqvist, C.; Boyle, R.; Crane, J.; Hogan, S.P.; Marsland, B.; Saglani, S.; Woodfolk, J.A.
Abstract: In the second of two linked articles, we describe the development in clinical as described by Clinical & Experimental Allergy and other journals in 2019. Epidemiology, clinical allergy, asthma and rhinitis are all covered. In this article, we described the development in the field of allergy as described by Clinical and Experimental Allergy in 2019. Epidemiology, clinical allergy, asthma and rhinitis are all covered.